PENJUAL JAMU KELILING DI KECAMATAN MALALAYANG KOTA MANADO - Budiantho, Jeine Dewi (HOLISTIK, Journal Of Social and Culture, 2014)
The informal sector is a safety in the construction sector in Indonesia, especially in solving work problems. This is due to the field in the informal sector, then there will be no unemployment. The informal sector is beginning to be recognized is an alternative to solve the problem of providing jobs. Informal workers especially Jamu Gendong Sellers are generally derived from the outskirts of Java. Jamu gendong is one that is widely consumed health drink for people of various social classes. With the jamu gendong, almost all people believe in the usefulness, especially for health. Prior to bloom and spread among the people of various herbs, of course jamu gendong is the main heir to believe in healing all kinds of diseases and of course make as health care. Jamu gendong can be estimated that the utilization is still high. The presence of the seller jamu gendong still visible in every hallway city of Manado. Under current conditions with a wide range of products offered instantly factories, sales jamu gendong can still survive because of the various ways or strategies undertaken jamu gendong sellers. The persistence jamu gendong because the price is relatively cheap and affordable, its sales were conducted door to door (door to door) so jamu gendong can survive, and pristine potion making sure buyers will quality and quality.Keywords : jamu gendong, health, informal